Stroke prevention in atrial fibrillation: An update on current management strategies - Hall, Toby; Stanton, T.; Wang, W.; Ng, A. (2013)
Stroke attributed to atrial fibrillation (AF) confers significant morbidity and mortality. In the past, warfarin has been the only successful stroke prevention agent available. However, it is often underutilized due to its well-known limitations, leaving many patients without adequate stroke protection. The last decade has seen significant strides forward in the field of anticoagulation for AF. The development of several novel oral anticoagulants that have superior efficacy, improved safety profile and fixed doses without the need for regular monitoring make them favorable as viable alternatives to warfarin. Improved risk scoring systems for both thromboembolism and bleeding have also allowed clinicians to better target patients most likely to benefit from these new therapies. In addition, non-pharmacological approaches to stroke prevention such as left atrial appendage exclusion devices may be useful in patients whom anticoagulation therapy is contraindicated. These new pharmacological and non-pharmacological options for stroke prevention in AF permit clinicians to tailor their management of patients according to individual needs and characteristics. The present review aims to outline the latest up-to-date management of AF in stroke prevention.